The Tradition of the Coal Tapai Party Increasing Cultural Value - Rosmawaty (Lakhomi Journal Scientific Journal of Culture, 2022)
This paper generally discusses and describes the Utilization of the Coal Tapai Party Tradition which aims to increase the cultural and educational values of students. This study is also expected to be a source of teaching materials in Indonesian subjects with local wisdom values and can provide strengthening character education for students. This study uses a type of descriptive writing with a qualitative approach. Data collection techniques include; literature study, which is a series of activities related to the methods of collecting library data, reading and taking notes and processing research materials. Further field studies which include; interviews, observations, and documentation studies. The data analysis technique used is data reduction, data presentation, and drawing conclusions. In checking the validity of the data, the researcher uses a triangulation technique where this technique is used to check the validity of the data using something else. The results obtained in this study are by utilizing the Tradition of the Coal Tapai Party, the Cultural and Educational Values of Students, especially at MTs Nurhasanah Labuhan Ruku, are increasing. The Tapai Party tradition is one of the unique and interesting traditions that is celebrated every year by the Batu Bara Malay community to welcome the holy month of Ramadan. This tradition contains many values that can be taught to students, including cultural and educational values. By knowing and utilizing tapai party traditions as teaching materials, students can increase cultural and educational values, love local cultural wisdom and can preserve it for the next generation.